ANALISIS KEBUTUHAN LUAS PARKIR KAMPUS I UNIVERSITAS MUHAMMADIYAH PURWOKERTO BERDASARKAN JUMLAH MAHASISWA - Anjarwati, Sulfah (UMP, 2012)
An increasing number of students affects accretion need for plots at the University of Muhammadiyah Purwokerto parking. This can be seen in the presence of a complex problem, one of which is the problem of vehicle parking space requirements are needed by students and employees who have a vehicle, either car or motorcycle. For that to know how the actual needs of the existing parking area, how the circulation patterns and parking should be applied to each parking area. Parking space requirements based on the obtained data on the number of students per faculty, the data is analyzed based on the Technical Guidelines for Operation of Parking Facilities issued by the Department of Transportation, the Director of Transportation land. After that made parking and circulation patterns tailored to the plots at the university campus I Muhammadiyah Purwokerto. Needs unit for motorcycle parking spaces is 761 SRP, and the need for car parking spaces is 25 SRP. Motorcycle parking pattern created the position of the vehicle is 900 because of the effectiveness of space. Patterns form a pattern of cars parked at an angle of 450 parking. because of the ease and comfort of the driver to maneuver in and out of parking space.Â Keywords: Needs Parking Space, Parking Space Unit